Control Of House Fly, Musca Domestica L. (Diptera: Muscidae) Population In Poultry Farms - Ong, Song Quan (2017)
House flies is the most important pest in poultry units. This study aimed to predict the population changes of house fly population and propose a control threshold, to evaluate the effectiveness of selected insecticide by comparing their LC50 between susceptible and wild strain, to determine the half-life and degradation rates of insecticides by spiking these insecticides into poultry manure, and to study the interaction between the Metarhizium. anisopliae (MET.) and the insecticides in order to control the house fly population. Population changes of house fly was first defined the knee points of a known population growth curve as a control threshold by comparing the rm of five densities of house flies in a simulated condition. Later, to understand the interactions between the larval and adult populations, the correlation between larval and adult capacity rate (rc) was studied.